2019
DOI: 10.2134/jeq2019.02.0091
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Release from Unamended and Gypsum‐ or Biochar‐Amended Soils under Simulated Snowmelt and Summer Flooding Conditions

Abstract: AGRICULTURAL WATER QUALITY IN COLD ENVIRONMENTS SPECIAL SECTION Core Ideas• Floodwater DRP concentration increased with time of flooding in amended and unamended soils. • Increase in floodwater DRP concentration was less under simulated snowmelt than summer flooding. • Rate of P diffusion from pore water to floodwater was less under simulated snowmelt flooding. • Gypsum reduced floodwater DRP in one soil with DRP concentrations >1 mg L −1 , but not in the other. • Woodchip biochar was ineffective in reducing P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(47 citation statements)
references
References 50 publications
8
39
0
Order By: Relevance
“…This is also clearly indicated by the highly significant ( P < .001) negative relationship between soil Eh and floodwater DRP concentration under warm flooding in all soils (Supplemental Table S4), whereas under cold flooding of frozen and unfrozen soils the relationship was weaker and often not significant. Consistent with these observations, previous studies reported significantly lower P release from flooded sediments at 7 °C than at 35 C (Sallade & Sims, 1997) and from frozen soils flooded at 4 °C than unfrozen soils flooded at 20 °C (Dharmakeerthi et al., 2019a), suggesting a lower redox‐induced P release under spring snowmelt than summer conditions.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…This is also clearly indicated by the highly significant ( P < .001) negative relationship between soil Eh and floodwater DRP concentration under warm flooding in all soils (Supplemental Table S4), whereas under cold flooding of frozen and unfrozen soils the relationship was weaker and often not significant. Consistent with these observations, previous studies reported significantly lower P release from flooded sediments at 7 °C than at 35 C (Sallade & Sims, 1997) and from frozen soils flooded at 4 °C than unfrozen soils flooded at 20 °C (Dharmakeerthi et al., 2019a), suggesting a lower redox‐induced P release under spring snowmelt than summer conditions.…”
Section: Discussionsupporting
confidence: 76%
“…Dharmakeerthi et al. (2019a) also reported a lower rate of P diffusion from pore water to floodwater under cold flooding of frozen soils compared with warm flooding of unfrozen soils.…”
Section: Discussionmentioning
confidence: 93%
“…To examine the temperature and freeze–thaw effects on P transfer from pore water to overlying floodwater, we explored the relationships between DRP concentrations in floodwater and pore water under SSF and IFT flooding conditions. Based on the temperature effect on P diffusion coefficient and findings from previous studies (Dharmakeerthi, Kumaragamage, Goltz, & Indraratne, 2019; MacKay & Barber, 1984; Tang et al., 2016), we expected an enhanced P diffusion under warm temperatures compared with cold temperatures; however, the same regression equation fitted the data under both SSF and IFT in the current study (Figure 3). The slopes for the separate regression equations developed for the SSF and IFT data (not shown in the figure) were not significantly ( P > .05) different.…”
Section: Resultssupporting
confidence: 65%
“…This is because the interaction between snowmelt and soil is generally low (Gray et al, 2001), leading to an assumption that the associated efficacy of soil nutrient management in reducing nutrient loads is also low, an assumption that is not supported by research (Liu et al, 2019a). In the Canadian Prairies, Dharmakeerthi et al (2019) test the effects of different soil amendments (i.e., gypsum and woodchip biochar) on P release from soil to pore water and floodwater under simulated spring snowmelt and summer flooding conditions. They find that gypsum amendment is very effective in reducing P release under both cold and warm conditions, but biochar is not.…”
Section: Management Options For Agricultural Water Quality In Cold CLmentioning
confidence: 99%